2020
DOI: 10.3389/fpubh.2020.00346
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Global Self-Rated Health and Happiness Measures Among Older People in the Yilan Study, Taiwan

Abstract: Background: Single-item measures of physical and mental health are feasible for older adults, but their validity for that age group is unclear. This study tested validity of a global self-rated health and a global self-rated happiness measure in a large sample of community-dwelling older adults in Taiwan. Methods: A cross-sectional sample of 3,982 men and women aged 65 or older in Yilan, Taiwan, provided data on global self-rated health and happiness using 100-point numerical scales. The Physical Component Sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…There is a vast amount of literature using self-reports of psychosocial cognitions using a single item. For example, a single-item question of happiness was positively associated with older age and negatively correlated with anxiety, indicative of a valid tool for population studies [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a vast amount of literature using self-reports of psychosocial cognitions using a single item. For example, a single-item question of happiness was positively associated with older age and negatively correlated with anxiety, indicative of a valid tool for population studies [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subjective well-being is a hot research topic in psychology and social science. Generally speaking, psychological researches focus on the psychological mechanisms by which humans obtain wellbeing, while sociological research focuses more on the external macro and micro factors that affect subjective well-being (25,26). In recent years, an increasing number of factors have been incorporated into the theoretical and empirical analyses of influences on subjective well-being.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…A study conducted in Central China has also found a positive relationship between self-rated health and older adults' subjective well-being (Zhang et al, 2008). Such a relationship has also been found among other Chinese population groups, such as Taiwanese and Chinese immigrants in the US (Kim et al, 2017;Lin et al, 2020).…”
Section: Literature Review Age Health and Happinessmentioning
confidence: 76%